2022
DOI: 10.3390/su14031503
|View full text |Cite
|
Sign up to set email alerts
|

Child Pedestrian Safety: Study of Street-Crossing Behaviour of Primary School Children with Adult Supervision

Abstract: Road traffic accidents are the primary cause of injuries and fatalities among children. The current study focuses on children’s (un)safe crossing behaviour in a real traffic situation accompanied by an adult at a crosswalk in front of their school. The study aims to investigate if there are differences in crossing behaviour related to road infrastructure (i.e., one-way and two-way street, elevated and non-elevated street crossing), the gender of the child, and the effect of the accompanying adult’s behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Ref. [11] has also suggested that education and training on safe crossing behavior in traffic can be a pedestrian protection measure. One of the most used pedestrian crossing types, a zebra crossing, was first designed and efficiently implemented in Slough, the United Kingdom, in 1951 [12].…”
Section: Literature Review 1traffic Safety On Pedestrian Crossingsmentioning
confidence: 99%
“…Ref. [11] has also suggested that education and training on safe crossing behavior in traffic can be a pedestrian protection measure. One of the most used pedestrian crossing types, a zebra crossing, was first designed and efficiently implemented in Slough, the United Kingdom, in 1951 [12].…”
Section: Literature Review 1traffic Safety On Pedestrian Crossingsmentioning
confidence: 99%
“…The statistical results indicated that 27.21% comply with the crossing policy, rules, and guidelines in the City of Kigali, whereas the remaining 72.79% do not. There is a need to improve the transportation system through infrastructural interventions and user training (Riaz et al, 2022). The summary model is written down as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The model employed the number of traffic accidents at community road intersections as the objective variable, and various factors as the explanatory variables, and the results clarified that the risk of accidents increased at four-way intersections with both poor and good visibility and at four-way intersections with narrow roads. Riaz et al investigated if there are differences in crossing behavior related to road infrastructure, the gender of the child, and the effect of the accompanying adult on primary school children crossing behavior [33]. They showed that girls were about 1.9 times more likely to stop before crossing as compared to boys, and adults holding hands with the child resulted in safer behaviors by children.…”
Section: Introductionmentioning
confidence: 99%